Inovasi Aksesoris Rambut Pengantin Berbasis Limbah Kulit Jagung: Studi Kelayakan Produk - Anik Maghfiroh; Nur Zuliana Rahmadhani; Ade Novi Nurul Ihsani; Trisnani Widowati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the feasibility of bridal hair accessories made from corn husk waste through sensory evaluation and preference testing. Corn husk was selected as an alternative material due to its environmentally friendly nature, biodegradability, and abundant availability as agricultural waste. The research subjects consisted of three expert validators with backgrounds in beauty and fashion design, as well as fifteen students from the Beauty Education Study Program as prospective users. Data were collected using structured observation sheets covering indicators of aesthetics, neatness, comfort, and functional suitability. The data were analyzed using descriptive percentage techniques. The results of the sensory evaluation showed an average score of 94.44%, which falls into the “highly feasible” category. Meanwhile, the preference test yielded a score of 92.12%, categorized as “highly favorable.” The developed accessories were considered visually appealing, comfortable to wear, and suitable for enhancing bridal hairstyles. These findings indicate that hair accessories made from corn husk waste are not only feasible in terms of aesthetics and technical aspects but also have strong potential to be developed as environmentally friendly products within the sustainable beauty and fashion industry.